Public acceptability of sustainable transport measures: A review of the literature - Alison Pridmore; Apollonia Miola (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2011)
Increasingly, the debate on transport policy involves the challenge of sustainable development. The concept of sustainable transport is derived from the general term of sustainable development. Sustainable transportation can be considered by examining the sustainability of the transport system itself, in view of its positive and negative external effects on: the environment; public health; safety and security; land use; congestion; economic growth; and social inclusion (OECD, 2000).
Keywords: 330